Buddhist responses to globalization - Kalmanson, Leah, 1977-; Shields, James Mark (Lanham, Maryland : Lexington Books, 2014)
This interdisciplinary collection of essays highlights the relevance of Buddhist doctrine and practice to issues of globalization. From various philosophical, religious, historical, and political perspectives, the authors show that Buddhism -- arguably the world's first transnational religion -- is a rich resource for navigating today's interconnected world. Buddhist Responses to Globalization addresses globalization as a contemporary phenomenon, marked by economic, cultural, and political deterritorialization, and also proposes concrete strategies for improving global conditions in light of these facts. Topics include Buddhist analyses of both capitalist and materialist economies; Buddhist religious syncretism in highly multicultural areas such as Honolulu; the changing face of Buddhism through the work of public intellectuals such as Alice Walker; and Buddhist responses to a range of issues including reparations and restorative justice, economic inequality, spirituality and political activism, cultural homogenization and nihilism, and feminist critique. In short, the book looks to bring Buddhist ideas and practices into direct and meaningful, yet critical, engagement with both the facts and theories of globalization
Part I: Globalization as Spatial, Cultural, and Economic Deterritorialization -- 1) Squaring Freedom with Equity: Challenging the Karma of the Globalization of Choice, Peter D. Hershock -- 2) Alice Walker, the Grand Mother, and a Buddhist- Womanist Response to Globalization, Carolyn M. Jones Medine -- 3) Religious Change as Glocalization: The Case of Shin Buddhism in Honolulu, Ugo Dessi -- 4) From Topos to Utopia: Critical Buddhism, Globalization, and Ideology Criticism, James Mark Shields -- Part II: Normative Responses to Globalization -- 5) An Inexhaustible Storehouse for an Insurmountable Debt: A Buddhist Reading of Reparations, Leah Kalmanson - - 6) Engaged Buddhism and Liberation Theologies: Fierce Compassion as a Mode of Justice, Melanie L. Harris -- 7) World, Nothing, and Globalization in Nishida and Nancy, John W.M. Krummel -- 8) A Zen Master Meets Contemporary Feminism: Reading Dogen as a Resource for Feminist Philosophy, Erin McCarthy.
Includes bibliographical references and index
Keywords: Buddhism -- Doctrines; Buddhism -- Social aspects; Globalization -- Religious aspects -- Buddhism